Coaching and Technology: Live Team Monitoring to Improve Training and Safety. (3rd September 2018) - Conners, Ryan T.; Whitehead, Paul N.; Shimizu, Tyler S.; Bailey, Jonathan D.
Abstract : Athletic coaches are always looking for the next strategy or tool to help them gain an advantage over their competitors. In recent years, technology has been incorporated into athletics at all levels. Heart rate monitors are a good example of equipment that has gained significant popularity for individualized training and recovery for athletes. However, a relatively new piece of equipment, the Polar Team Pro system (PTPS), takes technology to the next level by allowing for simultaneous analysis of a group of individuals. The PTPS incorporates global positioning system (GPS) tracking, motion tracking, live heart rate monitoring, and accurate data analysis to be used in a team setting. This article highlights how the PTPS can be used for smart coaching, player development, and safety monitoring of athletes, and provide a cost-effective coaching tool in today's sport setting.